Identification of CROWN ROOTLESS1‐regulated genes in rice reveals specific and conserved elements of postembryonic root formation. Issue 1 (1st December 2014) - Coudert, Yoan; Le, Van Anh Thi; Adam, Hélène; Bès, Martine; Vignols, Florence; Jouannic, Stefan; Guiderdoni, Emmanuel; Gantet, Pascal
Summary: In monocotyledons, the root system is mostly composed of postembryonic shoot‐borne roots called crown roots. In rice ( Oryza sativa ), auxin promotes crown root initiation via the LOB‐domain transcription factor (LBD) transcription factor CROWN ROOTLESS1 (CRL1); however, the gene regulatory network downstream of CRL1 remains largely unknown. We tested CRL1 transcriptional activity in yeast and in planta, identified CRL1‐regulated genes using an inducible gene expression system and a transcriptome analysis, and used in situ hybridization to demonstrate coexpression of a sample of CRL1‐regulated genes with CRL1 in crown root primordia. We show that CRL1 positively regulates 277 genes, including key genes involved in meristem patterning (such as QUIESCENT‐CENTER SPECIFIC HOMEOBOX ; QHB ), cell proliferation and hormone homeostasis. Many genes are homologous to Arabidopsis genes involved in lateral root formation, but about a quarter are rice‐specific. Our study reveals that several genes acting downstream of LBD transcription factors controlling postembryonic root formation are conserved between monocots and dicots. It also provides evidence that specific genes are involved in the formation of shoot‐derived roots in rice.